DIFFERENCES IN SLANG UNDERSTANDING IN GENERATION Z AND MILLENNIALS IN INDONESIA'S DIGITAL ERA - Bahagia Saragih; Rani Cristina Saragih; Halimah Azura; Ayu Nisca Gori; Tifani Yusmelia Zahra; Ramah Adriani Zura; Beby Aura Graicena (STKIP Subang, 2026)
This study aims to analyze the difference in slang comprehension between Generation Z and Millennials in the digital era. This study employed a quantitative method with data collection techniques through questionnaires distributed to 80 respondents. The number of respondents was divided into two groups consisting of 40 Generation Z and 40 Millennials. The results of the study show that Generation Z has a higher level of understanding of slang than Millennials. This is influenced by the intensity of digital media and social platforms such as TikTok, Instagram, and Twitter. Meanwhile, Millennials tend to be more familiar with the slang that developed in previous eras and have a lower understanding of the latest slang terms. The findings of this study indicate that technological developments play an important role in shaping language variation and intergenerational understanding. Therefore, this study emphasizes the importance of understanding generational differences in language use, especially in the context of digital communication.